If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6x + 3 = 2x + 18 Reorder the terms: 3 + 6x = 2x + 18 Reorder the terms: 3 + 6x = 18 + 2x Solving 3 + 6x = 18 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 3 + 6x + -2x = 18 + 2x + -2x Combine like terms: 6x + -2x = 4x 3 + 4x = 18 + 2x + -2x Combine like terms: 2x + -2x = 0 3 + 4x = 18 + 0 3 + 4x = 18 Add '-3' to each side of the equation. 3 + -3 + 4x = 18 + -3 Combine like terms: 3 + -3 = 0 0 + 4x = 18 + -3 4x = 18 + -3 Combine like terms: 18 + -3 = 15 4x = 15 Divide each side by '4'. x = 3.75 Simplifying x = 3.75
| 5u+5=26u | | -n-5(-6-7n)=-119 | | 25=7x-10 | | 8x+10=3x+15 | | 3y-3=5y-3 | | 2(x-3)+4x-(X+1)=3x+5(2x-3)-8 | | 2(10-5v)= | | 14-2x-16=5x-3x+34 | | 6(4z-2)=36 | | -40-8v=-5(1+3v) | | -7x-8y=-2 | | -39.6=12-0.4s | | 4x+9=-x+4 | | -17+16-x=16 | | 2y-x=y-5 | | 0.25+.05=6.10 | | 5b^2-22b-15=0 | | 18+8t=9(t-2) | | 3h-12=11h+4 | | 8(-9-2+3v-6v)= | | 2(4)-y=2 | | -6x-4(-7x-13)=58 | | 2(3)-y=2 | | y+2.6=6.9 | | 4x-22=54 | | -n-5(-6-7)=-119 | | 4x^2+20x+25=64 | | -9(1+6+6v)= | | 100=x+(x+2) | | 4h-4=8 | | 61.94+56.06-x-45=38 | | -3(-2+9v)= |